1986
DOI: 10.1111/j.1471-4159.1986.tb13016.x
|View full text |Cite
|
Sign up to set email alerts
|

Arginine‐Vasopressin Stimulates Inositol Phospholipid Metabolism in Rat Hippocampus

Abstract: The hippocampal vasopressin receptors have been characterised by measuring the stimulated accumulation of inositol monophosphate in the presence of 10 mM LiCl after hippocampal slices were prelabelled with [3H]inositol. Arginine-vasopressin caused a dose-dependent increase in inositol monophosphate accumulation (ED50 = 7.1 nM). The response was unchanged in the absence of Ca2+ and significantly reduced in the presence of a V1-receptor antagonist. Equimolar oxytocin was ineffective as a stimulus. This suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…This is in agreement with our previous findings that an antagonist of V1a-receptors, SR 49059, specifically inhibited the vasopressin-induced [Ca¥]é rise (Dayanithi et al 1996). In addition, studies on IP× accumulation measurements have shown that in many brain areas, vasopressin stimulation of the production of phosphatidyl-inositols is inhibited by a V1-type antagonist (Stephens & Logan, 1986;Moratalla et al 1988;Shewey & Dorsa, 1988;Hatton et al 1992). In the supraoptic nucleus, the vasopressin-induced [Ca¥]é increase is totally dependent upon extracellular Ca¥ but nevertheless is also significantly depressed by emptying the Ca¥ from intracellular stores by thapsigargin (Dayanithi et al 1996).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is in agreement with our previous findings that an antagonist of V1a-receptors, SR 49059, specifically inhibited the vasopressin-induced [Ca¥]é rise (Dayanithi et al 1996). In addition, studies on IP× accumulation measurements have shown that in many brain areas, vasopressin stimulation of the production of phosphatidyl-inositols is inhibited by a V1-type antagonist (Stephens & Logan, 1986;Moratalla et al 1988;Shewey & Dorsa, 1988;Hatton et al 1992). In the supraoptic nucleus, the vasopressin-induced [Ca¥]é increase is totally dependent upon extracellular Ca¥ but nevertheless is also significantly depressed by emptying the Ca¥ from intracellular stores by thapsigargin (Dayanithi et al 1996).…”
Section: Discussionsupporting
confidence: 81%
“…Little is known about vasopressin-induced intracellular transduction pathways in the brain. It has been reported that vasopressin increases the production of inositol phosphates in the hippocampus (Diaz-Brinton et al 1994;Stephens & Logan, 1986), in septum (Shewey & Dorsa, 1988;Lebrun et al 1990;Poulin & Pittman, 1993) and in dorsomedial medulla oblongata (Moratalla et al 1988). In other studies, the vasopressin failed to activate adenylate cyclase (AC) in hippocampus and septum (Barberis, 1983;Dorsa et al 1983;Audigier & Barberis, 1985;Brinton & McEwen, 1989).…”
mentioning
confidence: 97%
“…Brinton and McEwen (17) demonstrated that AVP enhanced the cAMP accumulation induced by norepinephrine in cultured hippocampal neurons, whereas OT did not. Similarly, it has been reported that 10 Ϫ7 M AVP leads to IP 3 production in rat hippocampal slices via V 1 receptors, whereas OT has no affect (15). Both AVP and OT at the concentration of 2.5 ϫ 10 Ϫ7 M induced IP 3 production in cultured hippocampal neurons, but these affects were exerted through the V 1 receptor (16).…”
Section: Or V 2 Receptor-mediated Inhibitory Actions On I Gly -mentioning
confidence: 58%
“…In both electrophysiological (9,11) and behavioral (13,14) studies, the effect of AVP was blocked by a selective V 1 receptor antagonist. It has also been reported that AVP induced the production of IP 3 through the V 1 receptor in rat cultured hippocampal neurons (15,16). Brinton and McEwen (17) demonstrated that AVP potentiates the norepinephrine-induced cAMP accumulation in a calcium-dependent manner in the rat hippocampal slice preparation through the V 1 receptor.…”
mentioning
confidence: 91%
“…Muscarinic agonists have been demonstrated to stimulate hydrolysis of PtdInsP2 in this tissue (Stephens & Logan, 1989a) leading to rapid formation of several inositol phosphates including Insl,4,5P3 and Insl,3,4,5P4 (Stephens & Logan, 1989b (Stephens & Logan, 1986 Incubations were terminated by addition of 250p1 of ice-cold pefchloric acid (10%w/v) and put on ice for 1Omin.…”
Section: Introductionmentioning
confidence: 99%